BOOK SCIENCE AND DOCUMENTATION DOCTORAL STUDIES AT VILNIUS UNIVERSITY IN 1991−2014 - NAVICKIENĖ, AUŠRA (Knygotyra, 2014)
The research in Book Science, Bibliography Science, History of Script and Writing, Documentology and Archivistics has a long tradition in Lithuania and today is perceived as an independent scientific branch of the Communication and Information Sciences. The main academic institution, engaged in publishing research and preparation of scholars concerned with these issues, today is the Institute of Book Science and Documentation of Vilnius University. Since 1991 it is a part of the Faculty of Communication, a new academic body/ construct of the university, which is responsible for developing doctoral studies in the field of Communication and Information Sciences. The objective of this article is to analyse the input of the Institute of Book Science and Documentation in the third cycle degree studies and to identify the strengths, weaknesses, opportunities, and threats while planning future training of scholars. The key research sources are: documentation governing doctoral studies (Law of the Republic of Lithuania on Education and Studies, regulations governing doctoral studies at Vilnius University, rules governing doctoral studies in the field of Communication and Information Sciences (CIS), CIS doctoral study programmes and descriptions of disciplines, PhD student lists, they publication indexes and different archival documents of doctoral studies at the Institute of Book Science and Documentation and the Faculty of Communication. The conclusions of the report are based on the examination of the data collected from primary sources and the SWOT analysis of the phenomenon in question. The analysis of the experience acquired through several decades reveals achievements and limitations of the third level degree studies in publishing as well as the peculiarities of development of research schools in Communication and Information Sciences in Lithuania.